Non-specialist delivery of the WHO Caregiver Skills Training Programme for children with neurodevelopmental disorders: stakeholder perspectives about acceptability and feasibility in rural Ethiopia - Kebede, Tigist Zerihun (Department of Psychiatry and Mental Health, 2023)
Background: Autism and other neurodevelopmental disorders (NDD) are common in low- and middle-income countries (LMIC). However, services to address the needs of this group in LMIC are almost non-existent. The World Health Organization (WHO) developed the Caregiver Skills Training (CST) programme to be suitable for delivery in diverse global contexts. Ethiopia, the country of focus in this study, has a largely rural population and a lack of specialist service providers. Additional contextual challenges, including poverty, low literacy, limited access to healthcare and a lack of specialist child mental health services, may undermine the delivery of CST in this setting. This thesis, therefore, seeks to explore the acceptability and feasibility of non-specialist delivery of the WHO-CST from the perspective of providers and caregivers in rural Ethiopia. Methods: In Chapter one, a general literature review of neurodevelopmental disability and caregiver skills training is presented, with a focus on sub-Saharan Africa, to help contextualise the main qualitative study, outlined in chapter two. In-depth interviews were conducted with caregivers (n=19) who were all participants in two rural pilot studies of the WHO-CST programme. In addition, three focus group interviews were conducted with non-specialist facilitators (n=8), who facilitated the CST programme in two rural pilot tests. Data were analysed using the framework approach. Results: Findings were mapped onto the three framework themes created for this analysis: 1) Programme content: caregivers and facilitators uniformly indicated that the adapted programme addressed a need and was relevant for their context; caregivers emphasised how the programme helped them understand their child's problems and improve their skills to support their children; facilitators highlighted having acquired new knowledge and skills relating to NDD; 2) Programme facilitation: caregiver responses suggested that programme facilitation by non-specialists was acceptable; non-specialist facilitators emphasised the importance of support and supervision for the facilitators and simplification and modification of some concepts, such as the concept of play, and 3) CST training approach and delivery: participants indicated that the training modalities, including home visits and group training, were acceptable and feasible in the local context. Conclusions: This study suggested that, with some contextually appropriate modifications of programme content and delivery and continuing supervision of facilitators, the WHO-CST programme facilitated by non-specialists would be acceptable and feasible in rural Ethiopia. Results from this study may be useful to fine-tune the implementation of non-specialist delivery of the CST programme in Ethiopia, as well as other LMIC.